The effect of application learning strategy type Share knowlight Activities and student learning result - Yurnalis Yurnalis (Fakultas Sastra Universitas Ekasakti, 2018)
In mathematics learning, active participation of students and interaction between students and teachers is a very important thing to get good learning outcomes. Based on the results of initial interviews concluded that still encountered some obstacles in teaching and learning activities. Among them the level of students' understanding of the taught material is still lacking, the interest and motivation to learn the mathematics of students is still low, the students tend to be passive in learning, do not want to ask the teacher. Even to ask friends was reluctant because students who are smart do not want to share with friends. So on this occasion, put forward a learning that is active learning strategy of sharing type of knowledge actively. The purpose of this research is to know how student activity in learning mathematics by using active learning strategy active type of knowledge sharing and to know whether student learning result of mathematics with Using active learning strategies active type of knowledge sharing is better than the result of learning mathematics students without using active learning strategies active type of knowledge sharing. The type of research is experimental research. The design used is Randomized Control Group Only Design. The result of this study is the result of student learning in the cognitive domain obtained through the test of learning achieves the percentage of completeness 86.36%, student activity as a whole is implemented and tends to increase in every meeting. Analysis of final test result data is done using t-test. After t test for hypothesis testing, thount = 2.69, ttable = 1.68, it turns out thount > ttable so that H0 is rejected, thus the result of mathematics learning in students using Active Knowledge Sharing Active Knowledge strategy is better than result Learning of students without using Active Learning Strategy Active Knowledge Sharing type.